Beer fermentation modeling for optimum flavor and performance. Issue 1 (2022) - Yerolla, Raju; Mehshan K M, Mohammed; Roy, Nevin; Harsha, Nekkanti Sri; Pavan Ganesh, Myreddy Prudhvi; Besta, Chandra Shekar
Abstract: Beer has been around for millennia. Fermentation is the most vital. Over time, fermenting technology has advanced. Wheat, barley, and other grains were used. Despite the same ingredients, each beer is distinct. Making beer requires a carbohydrates supply and yeast. Microbes help brewers from raw material production through packaging stability. Others degrade beer since it is created by fermenting food. Temperature affects acids, higher alcohols, and esters. Temperatures during fermentation can increase acidity and fruitiness. The goal of this paper is to develop a flavor model based on available literature. In addition, build the growth model in MATLAB and compare it to industry data to establish the essential kinetics involved in taste development.